The Influencing Factors and Cross-Cultural Adaption: Chinese Workforce in Lao People’s Democratic Republic - SAITHIBVONGSA, Phothong; LARKHAMSAI, Souphavady (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
Cross-cultural adaption is a challenging issue for expatriates and foreign workforce in different cultural settings. Lao PDR is a country shared border with China and there are a number of Chinese-invested companies and projects in this country. As a result of this, Chinese workforce is also dispatched to work for these Chinese invested companies and projects in Laos. The main objective of this empirical research is to examine the influences of language barrier, working environment and organizational structure on cross-cultural adaptation among Chinese workforces in Laos. Another key objective is to investigate the role of cultural and language training in moderating the relationship of three main independent variables (language barrier, working environment, organizational structure) and independent variable (cross-cultural adaptation). The questionnaire form is used to collect data from 448 samples who are Chinese workers at Chinese invested enterprises in Laos. The collected data is analyzed by both IBM SPSS v.23.0 and IBM AMOS v.21.0 for proving the proposed hypotheses. The research findings show that language barrier negatively affects cross-cultural adaption among Chinese workforces in Laos. Additionally, it was also found that working environment and organizational structure also play a crucial role in facilitate the cultural adaptability of Chinese workers. Interestingly, cultural and language training significantly moderate the influences of language barrier and working environment on cross-cultural adaptation. Surprisingly, there is no moderating effect of cultural and language training on the relationship between organizational structure and cross-cultural adaptation in the context of Chinese workforce in Laos. In short, this research is implemented in the same period as COVID 19 epidemic in Laos. Online data collection and virtual interview are frequently used. Therefore, some limitations emerged especially limited sample size, incomplete data collection, missing data, and bias issue. As a result of this some recommendation and suggestions are also provided for the future research. The findings provide valuable insights for policymakers and companies in designing training and support programs to improve expatriate adaptation.